PATTERN OF THYROID NEOPLASMS IN NELLORE AREA – A CLINICOPATHOLOGICAL CORRELATION - DR. DOST MOHAMED KHAN; DR.V.V.L SRIVIDHYA; DR. MANIMARAN.D; DR. B.A RAMAKRISHNA (International Journal of Pharma and Bio Sciences, 2013)
Thyroid tumours in a population can be compared to an iceberg – partly visible (clinically evident tumours) but mostly hidden (occult tumours). This study was done to evaluate histological features of various thyroid neoplasms with cytological and clinical correlation.The material for the present study included resected biopsy specimens of the thyroid lesions, submitted to the Department of Pathology, Narayana Medical College Hospital, Nellore, between August 2006 to July 2008. The details of each case were obtained from the clinical records.A total of (293) Two hundred & ninety three cases of Fine needle aspiration cytology and diagnosis were performed in all the cases. Two cases were reported as Thyroglossal cyst. Excluding these 2 cases, 242 cases (83.16%) were diagnosed as Non-neoplastic and 49 cases (17%) as Neoplastic. Out of these 293 cases , only 102 patients underwent surgical excision and so a histopathological correlation was obtained in all 102 cases. Out of 102 cases, Non-neoplastic lesions of thyroid were seen in 52 cases (51%) and Neoplastic lesions in 50 cases( 49%), which are nearly equally distributed. Out of 49cases of cytologically proven neoplasms , 48 correlated with histopathology cases showed similar neoplasms. The histological correlation was 98% and the overall accuracy was 98.63% and sensitivity was 95%.Non- neoplastic lesions and neoplastic lesions were are equally distributed. Correlation between Fine needle aspiration cytology and histopathology can improve sensitivity & specificity of diagnostic accuracy of thyroid lesions.Performing Fine needle aspiration prior to biopsy is effective.